RÁBA – Running Down a Dream: The Hungarian Mission in North Africa, Egypt - Horváth, Borbála (Journal of Central and Eastern European African Studies, 2025)
This article aims to introduce to the reader the story of the RÁBA Hungarian machinery factory and its connections to North-Africa. As the RÁBA consortium was one of the largest industrial company in Hungary from the beginning of the 20th century, it surely has a long history with Africa to be told. The article firstly gives a historical review of the company, then it turns to describe the role of the machinery factory in the international trade and then the life of the famous Mr. Ede Horváth (CEO of RÁBA), a relative of the author gets to be examined. The article then takes every era of Egyptian politics (the Infitāh with Sadat, the Mubarak years), and continues to describe the business the company made with the country. After concluding the findings, there is an interesting appendix with the memoirs of the author which colours lively the experiences and thoughts of the author. The theme is very actual and with its interesting forms and stories that it includes is more than recommended for the reader. The article’s aim finally is to give a comprehensive picture about the Soviet era’s businesses between Hungary and Africa, which it surely describes well enough.